Proceedings of the 2017 2nd International Symposium on Advances in Electrical, Electronics and Computer Engineering (ISAEECE 20 2017
DOI: 10.2991/isaeece-17.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Key Elements of Sulfide Modification in the Sulfur-based Free-cutting Steel

Abstract: Sulfides are beneficial inclusion in free-cutting steel, and can cause chips to break easily as an internal source of stress concentration when cutting steel, and also lubricate the tool and workpiece, thus reducing tool wear and improving machinability. Sulfide morphology directly determines the performance of the free-cutting steel, and it is possible to improve the machinability of the free-cutting steel by changing the MnS inclusions into small, dispersive, spherical or spindle-shaped inclusions, thus maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…[8,9,11] As the magnesium content increases, the evolution order of magnesium deoxygenation products is Al 2 O 3 !MA!Mg-Al-O-S!Mg-O-S. [12] In addition, due to the similarity in chemical reactions between Mg or Ca and Mn, it has been found that Mg or Ca can dissolve in MnS to form (Mn,Mg)S or (Mn,Ca) S. When they serve as the outer layer of the oxide, their cores are found to be MA and calcium aluminum spinel (CaAl 2 O 4 , CA), respectively. [13] However, composite MnS-MgS-CaS inclusions in steel containing high magnesium content were found to be irregular, [14] which is not conducive to improving the morphology of sulfides, due to the importance of sulfide in forming composite inclusions with oxides. Similarly, it is worth noting that the composition of magnesium oxides and sulfides is closely related to the precipitation of acicular ferrite in steel.…”
Section: Introductionmentioning
confidence: 99%
“…[8,9,11] As the magnesium content increases, the evolution order of magnesium deoxygenation products is Al 2 O 3 !MA!Mg-Al-O-S!Mg-O-S. [12] In addition, due to the similarity in chemical reactions between Mg or Ca and Mn, it has been found that Mg or Ca can dissolve in MnS to form (Mn,Mg)S or (Mn,Ca) S. When they serve as the outer layer of the oxide, their cores are found to be MA and calcium aluminum spinel (CaAl 2 O 4 , CA), respectively. [13] However, composite MnS-MgS-CaS inclusions in steel containing high magnesium content were found to be irregular, [14] which is not conducive to improving the morphology of sulfides, due to the importance of sulfide in forming composite inclusions with oxides. Similarly, it is worth noting that the composition of magnesium oxides and sulfides is closely related to the precipitation of acicular ferrite in steel.…”
Section: Introductionmentioning
confidence: 99%